Physical Activity to Stay Fit - Shadap, Arkierupaia (Journal of Health and Allied Sciences NU, 2020)
Physical activity is any bodily movement produced by skeletal muscles that require energy expenditure. According to World Health Organization, regular physical activities such as walking, cycling, doing the household work, etc., make an individual feel good and it has significant benefits for health. One of the vital elements for healthy bones at every age is exercise. Exercise lowers the blood pressure, slightly decreases the levels of total- and low-density lipoprotein—the bad cholesterol, and increases the levels of high-density lipoprotein—the good cholesterol. Regular physical activity and exercise help in maintaining the healthy body weight, decreasing stress, apprehension, and preventing depression. Exercising can also possibly help in delaying the effects of Alzheimer’s disease and other forms of dementia. Strong evidence shows that physical activity has a wide range of beneficial effects for both physical and mental well-being.
Keywords: physical activity; physical movement; exercise; health